The Perceptions and Attitudes of Students on the Intersectionality of Languages in Higher Education - Enid M Pitsoane; K Nyamakazi; M M Phora; G Sephula; D Lala; A Chauke (Jurusan Tadris Bahasa Indonesia, 2025)
This research investigates students’ perceptions and attitudes towards the intersectionality of language in the context of higher education in South Africa. Through a qualitative approach, the study collected data using semi-structured interviews involving fifteen participants from diverse linguistic and cultural backgrounds. The results of the thematic analysis revealed four key findings. First, the ongoing language barriers in the academic environment remain pronounced. Second, socio-cultural norms within communities have a significant influence on how individuals use language. Third, the implementation of multilingual policies advocated by institutions is still very limited and not optimal. Fourth, there is an urgency to build a stronger and more comprehensive support system for speakers from minority linguistic groups. Based on the theory of intersectionality, linguistic capital, and language ideology, this research shows how the enduring dominance of English continues to marginalize the role of indigenous languages and their speakers. These findings further underscore the significant gap between formally established language policies and the actual practices that occur on the ground. Therefore, systemic interventions are necessary to affirm and promote linguistic diversity. The conclusion of this study states that advancing multilingualism in higher education requires more than just written regulations. It demands the implementation of culturally responsive pedagogy, the availability of learning resources in various languages, and a genuine institutional commitment to achieving language equality. Without those supporting elements, multilingual policies will only be discourse without having any substantial impact.Persepsi dan Sikap Mahasiswa terhadap Interseksionalitas Bahasa di Pendidikan TinggiPenelitian ini menyelidiki persepsi dan sikap mahasiswa terhadap interseksionalitas bahasa dalam konteks pendidikan tinggi di Afrika Selatan. Melalui pendekatan kualitatif, studi ini mengumpulkan data menggunakan wawancara semi-terstruktur yang melibatkan lima belas orang peserta dari beragam latar belakang linguistik dan budaya. Hasil analisis tematik mengungkapkan empat temuan kunci. Pertama, hambatan bahasa yang terus-menerus terjadi di lingkungan akademik masih sangat terasa. Kedua, norma-norma sosial budaya dalam komunitas memiliki pengaruh yang signifikan terhadap cara seseorang menggunakan bahasa. Ketiga, implementasi kebijakan multilingual yang dicanangkan oleh institusi masih sangat terbatas dan belum optimal. Keempat, terdapat urgensi untuk membangun sistem pendukung yang lebih kuat dan komprehensif bagi para penutur dari kelompok linguistik minoritas. Dengan berlandaskan pada teori interseksionalitas, modal linguistik, dan ideologi bahasa, penelitian ini menunjukkan bagaimana dominasi bahasa Inggris yang masih sangat kental justru terus meminggirkan peran bahasa-bahasa pribumi serta para penuturnya. Temuan ini semakin menegaskan adanya kesenjangan yang lebar antara kebijakan bahasa yang ditetapkan secara formal dengan praktik nyata yang terjadi di lapangan. Oleh karena itu, diperlukan intervensi sistematis yang dapat mengafirmasi dan mempromosikan keanekaragaman bahasa. Simpulan dari studi ini menyatakan bahwa memajukan multilingualisme di perguruan tinggi memerlukan lebih dari sekadar peraturan tertulis. Hal ini menuntut diimplementasikannya pedagogi yang responsif secara budaya, ketersediaan sumber daya pembelajaran dalam berbagai bahasa, serta komitmen kelembagaan yang sungguh-sungguh untuk mewujudkan kesetaraan bahasa. Tanpa elemen-elemen pendukung tersebut, kebijakan multilingual hanya akan menjadi wacana tanpa memiliki dampak yang substansial.